Design Development of the Spiritual Tourism Destination Areas Ki Buyut Trusmi and Astana Gunungjati in the Cirebon Regency - Agustina, Ina Helena; Fauzi, Hilman; Ekasari, Astri Mutia (KnE Social Sciences, 2024)
There are a significant number of spiritual tourism destinations in the Cirebon Regency. Attractions include Ki Buyut Trusmi and Astana Gunungjati. To maintain the existence of these destinations, a study was conducted on the design development plans for the two regions, as well as an investigation on travelers who had visited the two tourist attractions. The purpose of this study was to describe the design development of the Ki Buyut Trusmi and Astana Gunungjati Spiritual Tourism Areas. The research method was carried out using a descriptive approach through pre-test and post-test techniques. Data collection was carried out from 10 selected people through purposive sampling, namely visitors who have visited both tourist destination locations. The questionnaire was filled by visitors before viewing the area development design (pre-test) and after viewing the area design (post-test). The results were then compared, and it can be concluded what designs are needed in the two locations of the area. The findings show which spatial elements from the two destinations can be developed. Keywords: design-destination-spiritual-tourism, Ki Buyut Trusmi-Astana Gunungjati, development